Reinterpreting the Function of Spouse in Marital Harmony in the Contemporary Era: A Hermeneutic Inquiry of Traditional Tafsīr and Iḥyā’ ‘Ulūm al-Dīn - Muhammad Farouq Auni Syafi; Kasman Kasman; Fawaiz Fawaiz (Alfuad: Jurnal Sosial Keagamaan, 2025)
The phenomenon of domestic harmony crises in modern society marked by spousal-role dysfunction, rising divorce rates, and disorientation of marital values constitutes an urgent contemporary religious issue that demanding rigorous examination. This study examines the islamic conception of marital harmony through a hermeneutic engagement with classical sources, notably as Imam al-Ghazālī's Iḥyā’ ‘Ulūm al-Dīn and exegetical works including Tafsīr al-Tabarī, Tafsīr Ibn Kathīr, and Tafsīr al-Qurṭubī, etc. Classical texts are reinterpreted by employing Gadamerian hermeneutics, within a dialogical framework between historical and social horizons to derive contemporary relevance. The results of the study demonstrate that the core of Islamic Principles sakinah (tranquility), mawaddah (affection), and rahmah (mercy) can be transformed into ethical-spiritual solutions for modern marital challenges, including authority crises, emotional instability, and digital cultural influences. Thus, hermeneutic analysis of classical texts not only revitalizes islamic values but also provides conceptual-practical foundations for establishing equitable, participatory, and transcendent households.